Potentials of informal street vending as a place making tool in Bandar Tasik Puteri, Selangor - Nurbaidura Salim,; Noor Syarafina Sallehudin,; Ammar Syazwan Shamsul Kamal, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The invention of street vendors in urban public places help in creating a living cultural enclave despite the robustness of street activities. This paper aims to explore the potentials of street vending as a place making tool in creating a dynamic public area. By choosing Bandar Tasik Puteri as a case study, this paper investigates how street vendors may help to create and improve the livelihood in a public place. The mixed method approach through site observation and questionnaire survey were adopted to capture tangible and intangible aspect of the study area. Findings of the study reveals that Bandar Tasik Puteri has a great potential for street vendor activities as it will improve quality of life of local community, foster social interactions and create dynamic public space within the area. However, several challenges need to be resolved beforehand, including limited space and regulatory issues. The paper highlights the importance of a supportive legislative framework and a collaborative approach among stakeholders to enable the long-term growth of street vending as a means of improving public spaces and boosting public participation.